The Role of Total Quality Management in Improving Health Services (An applied study on Saudi German Hospital in Asir) - Al Aown, Arwa Mohammed Abdullah; Aljumaai, Esraa Hussain Mohammad; Alqahtani, Aisha Sultan; Al Muhammed, Fatima Abdo Hassan; Mushey, Mariam Ali Abdullah (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of this research is to know the role of total quality management in improving health services in the Saudi German Hospital in Asir, and the research methodology was represented by the descriptive analytical approach. With several results, it is an agreement between the views of the study sample members towards the participation of the executive management in the hospital to improve the quality of the health service. The hospital administration deals with complaints submitted by patients with all care and seriousness, matching the service requested by the patient with the service provided. There are no statistically significant differences at the significance level (0.05) between the average of the respondents’ answers about the role of total quality management in improving the health services provided at the Saudi German Hospital in Asir due to the following variables (educational qualification, years of experience, job type). The results have several recommendations, the most important of which is paying more attention to the preventive measures available within the hospital to achieve the maximum benefit for the general health of patients. The administration should pay more attention to developing the cadres working inside the hospital towards their commitment to the required quality that satisfies the patients’ desires for the hospital to reach the highest levels of perfection and perfection.